Cenozoic Climate History from Seismic Reflection and Drilling Studies on the Antarctic Continental Margin - Cooper, Alan K; Brancolini, Giuliano; Escutia, Carlota; Kristoffersen, Yngve; Larter, Rob; Leitchenkov, German; O'Brien, Phillip; Jokat, Wilfried (Developments in Earth and Environmental Sciences, 2008)
Keywords: Antarktis; geomorfologi; innlandsis; isbreer; kontinentalmargin; paleoseanografi; stratigrafi

Polar exploration - Huntford, Roland (Two planks and a passion : the dramatic history of skiing, 2008)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; skihistorie; utstyr

Temperature effects on biodegradation of petroleum contaminants in cold soils - Rike, Anne Gunn; Schiewer, Silke; Filler, Dennis M (Bioremediation of Petroleum Hydrocarbons in Cold Regions, 2008)
Bioremediation in cold climates is frequently regarded with skepticism. Owners of polluted sites and regulatory agencies may doubt the effectiveness of biological degradation at near freezing temperatures. While it is true that biodegradation rates decrease with decreasing temperatures, this does not mean that bioremediation is inappropriate for cold regions. Microbial degradation of hydrocarbons occurs even around 0 °C (Chapter 4). In remote alpine, Arctic, and Antarctic locations, excavation and shipping of contaminated soil may be prohibitively expensive. Bioremediation may be the most cost-effective alternative. This chapter discusses microbial adaptation to cold temperatures as well as results of laboratory and field studies of bioremediation at low temperatures.Microorganisms can grow at temperatures ranging from subzero to more than 100 °C. Microbes are divided into four groups based on the range of temperature at which they can grow. The psychrophiles grows at temperatures below 20 °C, the mesophiles between 20 °C and 44 °C, the thermophiles between 45 °C and 70 °C, and the hyperthermophiles require growth temperatures above 70 °C to over 110 °C. The term “cold-adapted microorganisms” (CAMs) is frequently used for describing bacteria growing at or close to zero degrees Celsius. Depending on the cardinal temperatures (the minimal, the optimal, and the maximum growth temperature), CAMs can be classified as psychrophiles or psychrotrophs. Morita's (1975) definition, which holds that psychrophiles have a maximum growth temperature of less than 20 °C and an optimal growth temperature of less than 15 °C, while psychrotrophs have a maximum temperature of 40 °C and an optimal growth temperature higher than 15 °C, is widely accepted.
Keywords: Antarktis; biodiversitet; forurensning; polarområdene; økologi; økosystemer

Helse og helbred sønnafor verden. Litt om legetjenester og helsetilstand blant hvalfangere - Ringstad, Jan Erik (Mdisinhistorie til sjøs, 2008)
Keywords: Sørishavet; helsevesenet; hvalfangere; hvalfangst; pelagisk

Contamination, regulation, and remediation: an introduction to bioremediation of petroleum hydrocarbons in cold regions - Snape, Ian; Acomb, Larry; Barnes, David L; Bainbridge, Steve; Eno, Robert; Filler, Dennis M; Plato, Natalie; Poland, John S; Raymond, Tania C; Rayner, John L; Riddle, Martin J; Rike, Anne G; et al. (Bioremediation of Petroleum Hydrocarbons in Cold Regions, 2008)
Oil and fuel spills are among the most extensive and environmentally damaging pollution problems in cold regions and are recognized as potential threats to human and ecosystem health. It is generally thought that spills are more damaging in cold regions, and that ecosystem recovery is slower than in warmer climates (AMAP 1998; Det Norske Veritas 2003). Slow natural attenuation rates mean that petroleum concentrations remain high for many years, and site managers are therefore often forced to select among a range of more active remediation options, each of which involves a trade-off between cost and treatment time (Figure 11). The acceptable treatment timeline is usually dictated by financial circumstance, perceived risks, regulatory pressure, or transfer of land ownership.In situations where remediation and site closure are not urgent, natural attenuation is often considered an option. However, for many cold region sites, contaminants rapidly migrate off-site (Gore et al. 1999; Snape et al. 2006a). In seasonally frozen ground, especially in wetlands, a pulse of contamination is often released with each summer thaw (AMAP 1998; Snape et al. 2002). In these circumstances natural attenuation is likely not a satisfactory option. Simply excavating contaminants and removing them for off-site treatment may not be viable either, because the costs are often prohibitive and the environmental consequences of bulk extraction can equal or exceed the damage caused by the initial spill (Filler et al. 2006; Riser-Roberts 1998).
Keywords: Antarktis; biodiversitet; forurensning; polarområdene; økologi; økosystemer